2019
DOI: 10.18280/eesrj.060401
|View full text |Cite
|
Sign up to set email alerts
|

Bush Mango (Irvingia spp.) As an Important Alternative Livelihood Source for the Indigenes of the Korup National Park Communities, South West Cameroon

Abstract: Protected resources continue to suffer illegal exploitation due to inadequate alternative livelihood options to the local populations. This study evaluated bush mango current situation in Korup National Park Communities (KNPCs). Five villages were selected based on high productivity. Focused group discussion was done in each village to identify stakeholders in the bush mango sector. Ninety-four household questionnaires administered to collectors. All collectors exploited rainy season bush mango; 36 (38%) colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As a result, the concept of privately owned tree crops producing Agroforestry Tree Products (AFTPs) has been proposed to distinguish them from common-property forest resources [207]. This is important, as these tree products are the backbone of most rural economies and contribute to the enhancement of the socio-economic welfare of forestdependent communities [180,187,189,191,[208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224]. Furthermore, studies have demonstrated that the sustainable exploitation, commercialization and management of NTFPs/AFTPs could contribute immensely to the attainment of important Sustainable Development Goals (SDGs) such as SDG 2 (zero hunger), SDG 3 (good health and wellbeing), SDG 13 (climate action) and SDG 15 (life on land) [21,[225][226][227].…”
Section: Governance Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the concept of privately owned tree crops producing Agroforestry Tree Products (AFTPs) has been proposed to distinguish them from common-property forest resources [207]. This is important, as these tree products are the backbone of most rural economies and contribute to the enhancement of the socio-economic welfare of forestdependent communities [180,187,189,191,[208][209][210][211][212][213][214][215][216][217][218][219][220][221][222][223][224]. Furthermore, studies have demonstrated that the sustainable exploitation, commercialization and management of NTFPs/AFTPs could contribute immensely to the attainment of important Sustainable Development Goals (SDGs) such as SDG 2 (zero hunger), SDG 3 (good health and wellbeing), SDG 13 (climate action) and SDG 15 (life on land) [21,[225][226][227].…”
Section: Governance Issuesmentioning
confidence: 99%
“…Essougong et al [32] reported that, on average, Rural Resource Centres organized 40 training sessions annually, reaching 1444 farmers in Cameroon. It was observed that a single Relay Organization was supporting on average 100-240 farmers to acquire essential domestication skills, such as the vegetative propagation techniques, as well as tree planting, management and harvesting techniques [223]. To enhance organisational and financial sustainability of this extension and capacity building approach, other activities include social networking between Centres as well as their private and institutional clients, development partners, local research teams and municipalities [34].…”
Section: Upscaling and Capacity Building-the Role Of Rural Resource C...mentioning
confidence: 99%